Матеріали до «Словника граматичного керування прикметників» - Габай, А. (Лексикографічний бюлетень, 2011)
The article is devoted to theoretical bases and principles of compilation of the first modern Ukrainian linguistic Dictionary of adjectival grammatical government. The structure of vocabulary entries is thoroughly described. The specimens of the vocabulary entries of grammatical government of gualitative adjectives are offered.